Inovasi Pelayanan Pertanahan Pengecekan Sertifikat online - Rona Yunita Nugraheni; Budi Puspo Priyadi; Kismartini Kismartini (Universitas Medan Area, 2021)
The development of science and technology in this era is increasingly rapid, it encourages the government to make changes and innovations to realize good governance, one of which is in terms of public services. One form of public service in Indonesia is land. The Ministry of Agrarian Affairs and Spatial Planning / National Land Agency as a government agency responsible for land affairs make innovations through the West Kotawaringin Regency Land Office as a tangible manifestation of good governance in land services namely online certificate checking services to provide services that facilitate the community. The purpose of this study is to analyze how the implementation of the online certificate checking service innovation and what factors influence it. This type of research used in this research is descriptive research with a qualitative approach. The results showed that the innovation of online certificate checking services improved the performance of the West Kotawaringin Regency Land Office, which was faster, more precise, transparent and accountable in providing services to applicants. Internal factors that influence are vision and strategy, human resources, organizational structure and organizational culture. External factors that influence are technology, government policies and natural conditions.